Systematic Mapping on Internet of Things' Client-Sided Development - Figueira Goncalves, Rafael; Menolli, André; Marcelino Dionisio, Gustavo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2022)
Context: the Internet of Things (IoT) is a paradigm that provides an ecosystem for a fast-growing quantity of connected devices, also defined as cyber-physical devices. Problem: the creation of Internet of Things solutions is fairly complex, having to integrate and communicate between sensors, devices, and larger systems, presenting many technical challenges not present in the same magnitude as other paradigms. One of the most affected segments is the development of cyber-physical devices. Much of its development energy is spent on the connecting and efficacy of these devices, often overlooking the future impacts of the proposed solution, caused by a lack of software quality. Solution: The execution of a Systematic Mapping in order to bring attention to possible research gaps. SI Theory: This work follows the accepted protocols for systematic mappings, meta-analysis, and Hermeneutics. Methodology: this paper executes a systematic mapping, following well-accepted guidelines in order to systematically gather, include and classify scientific papers according to IoT devices’ own characteristics. Results: 8146 studies were found and reduced to 211 relevant studies that focused on client-side IoT development had their data graphed and analyzed. Our results show a lack of software metrics used, many research gaps and correlations were discovered, when in respect to specific software quality properties as described by the ISO25010 and other characteristics collected, such as programming languages and study domain. Contributions: The main contribution of this study is to expose multiple research gaps present in IoT client-side development. Providing a background for future information system studies on techniques and tools to improve IoT development.